Earnings management to avoid losses and earnings declines in Croatia. (3rd June 2019) - Degiannakis, Stavros; Giannopoulos, George; Ibrahim, Salma; Rozic, Ivana
This paper provides empirical evidence that Croatian companies manage reported earnings to avoid losses and earnings declines. Specifically, we find that the cross-sectional distribution of scaled earnings and changes in earnings show high frequencies of small positive earnings and small increases in earnings while the frequencies of small losses and small decreases in earnings are less frequent. Furthermore, we demonstrate that these discontinuities are likely due to discretionary accruals. We examine the frequency distribution of reported earnings after removing discretionary accruals and find that the cross-sectional distributions of non-discretionary scaled earnings show lower frequencies of small positive earnings and higher frequencies of small negative earnings. Additionally, the cross-sectional distribution of non-discretionary change in earnings demonstrates mixed frequencies of non-discretionary changes in earnings. Overall, this paper adds new empirical evidence to the benchmark-beating literature by demonstrating international evidence of earnings management around zero earnings and zero earnings changes benchmarks.